Essential medicines wastage assessment in the Solomon Islands. - Ibrahim Dadari; Effua Usuf (Public Library of Science (PLoS), 2022)
The World Health Organization (WHO) regularly updates its list of Essential medicines. However, the use of these medicines in the Solomon Islands is less well described. We assessed supplies, prescriptions, and stocks of zinc, oral rehydration salt (ORS), vitamin A, and albendazole in six provinces of the Solomon Islands for 2017 and 2018. We also conducted a stocktake of available medicine supplies at the point of data collection. We found that quantities of drugs supplied were in excess of the prescriptions and stock records at the facilities were inadequate. There were expired drugs at the facilities. Out of the 20 health facilities with available data, 11 (55%), 3 (15%), and 1 (5%) had expired stock of ORS, albendazole and vitamin A respectively. No expired zinc tablets were recorded. A revision of the medicines stock management system is necessary to adequately quantify essential medicine wastage and improve the stock management in the Solomon Islands.